Agronomic behavior and chemical composition of three varieties of grasses at different harvest ages - Cabezas Congo, Ronald (2025)
The study investigated the impact of age (E) and variety (V) on several plant characteristics, including plant height (AP) in centimeters, forage biomass (FB) in kilograms of dry matter per hectare, stem weight (PT), leaf number (LH), leaf area (LA), leaf-stem ratio (LSR), and the chemical composition of three grass species: Axonopus micay, Axonopus scoparius, and Melinis minutiflora. The grasses were harvested at five different stages of maturity (30, 45, 60, 75, and 90 days). A randomized complete block design with a factorial arrangement (3 x 5) was employed, resulting in a total of 75 plots. Notably, the purple Gramalote grass (Axonopus scoparius) outperformed the other varieties in terms of AP, PT, LH, AH, PH, and H:T ratio, with specific measurements of 168,46 cm, 97,24 g, 64,02 cm, 3,72 cm, 32,39 g, and 0,37, respectively. Additionally, at 90 days, the highest values were observed for AP (138,83 cm), PT (58,96 g), LH (41,74 cm), AH (2,94 cm), PH (15,69 g), and biomass (1 682,5 kg MS ha-1). Furthermore, the dry matter content (%) of the purple Gramalote grass (33,16) exceeded that of the Gordura grass (32,38) and Micay grass (21,97). In terms of ash and crude protein content, the Gramalote morado variety exhibited higher values (9,65 and 9,09 respectively).